Expelling Slavery from the Nation: Representations of labour exploitation in Australia’s supply chain - Szörényi, Anna (Anti-Trafficking Review, 2016)
On 4 May 2015, the Australian national broadcaster’s current affairs programme Four Corners aired an episode titled ‘Slaving Away: The dirty secrets behind Australia’s fresh food’, that provided revelations of labour exploitation of migrant workers on working holiday visas. The government reacted swiftly to these allegations with an ‘operation’ ostensibly designed to stop the exploitation. In reports of Operation Cloudburst, however, there was a shift in the media’s definition of the problem: worker exploitation became visa violations and newspapers shortly reported the resulting action taken: the ‘illegal workers’ in Australia’s food industry had been arrested. This paper tracks the competing discursive and visual representations of this case that ultimately made questions of labour rights become questions of immigration, making it plausible and acceptable that concern over exploitation of workers should be addressed by deportation of ‘illegal immigrants’. Such discursive slippage is enabled by cultural amnesia over Australia’s history of exploitation of racialised and migrant labourers, which allows ‘slavery’ to be represented as a ‘foreign’ problem that can be expelled in defence of the purity of the national domestic space.